TERRITORIAL COMMUNITY DEVELOPMENT MANAGEMENT ON THE BASIS OF A PROJECT APPROACH: EXPERIENCE, INSTRUMENTS AND FINANCING - Polyanska, Alla; Zapukhliak, Ivanna; Verbovska, Lesya (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article proves that the project activity of territorial communities is an effective mechanism of their development. It is substantiated that the application of project management in the activities of local communities is one of the modern tools to ensure sustainability and competitiveness. The main arguments for the feasibility of applying the concept of project management for the development and implementation of programs and projects in the field of public administration and local development. The paper presents a successful example of the implementation of decentralization reforms in the Republic of Poland. It has been studied that communities feel important, but due to the lack of qualified project management professionals they cannot make quality use of the resources and tools to which they have access at this stage. Lack of resources does not allow the local community to be realized at full capacity. A number of factors that determine the need for use and effectiveness of project management in the activities of local communities are considered. Among such factors, organizational and legal factors, publicity factor and environmental factor are singled out. In the study, in addition to international technical assistance programs and the State Fund for Regional Development, the authors present a number of other opportunities to raise funds from the community, such as common cost, endowment and fundraising. The article presents the results of the author's study of the project activities of local communities, which was conducted through gooleform. According to the results of the study, local communities are ready to train their staff, raise funds from various sources, and introduce new tools and practices. It is proved that the effective use of project activities in communities will increase the competitiveness of the community, implement the necessary services to the community, carry out the necessary modernization of funds and property that moved to the community after the merger.